Levelling the Playing Field: Sport for Development - Lennox, Elizabeth (Université d'Ottawa | University of Ottawa, 2013)
In recent years, sport has moved from the periphery to the very centre of the development debate. Sport for development has acquired increasing importance in a number of arenas: the United Nations has created a Sport for Development and Peace Office, countless scholars have extolled the virtues and condemned the shortcomings of the movement, and hundreds of organizations have established sport for development programs across the Global South and throughout disadvantaged pockets in the North. This paper examines the sport for development movement, its history and the claims and realities surrounding the movement. Three case studies will be examined to look at sport for development programs that are undertaking development work in different ways within the movement: the plus sport program in Zambia being run by the government through the educational sector, the plus sport Right to Play program being implemented by an international NGO, and the sport plus Mathare Youth Sports Association (MYSA) grassroots program. This paper will argue that sport for development programs are doing development differently, reaching beyond traditional neo-liberal structures and having a measurable impact, particularly in terms of gender equity, in the Global South.